Pancreatic Metastasis from Prostate Cancer - Julian Jacob; Cyrus Chargari; Olivier Bauduceau; Maryse Fayolle; Bernard Ceccaldi; Frédéric Prat; Sylvestre Le Moulec; Lionel Vedrine (Case Reports in Medicine)
The pancreas is an unusual location for metastases from other primary cancers. Rarely, pancreatic metastases from kidney or colorectal cancers have been reported. However, a variety of other cancers may also spread to the pancreas. We report an exceptional case of pancreatic metastasis from prostate cancer. Differences in management between primary and secondary pancreatic tumors make recognition of metastases to the pancreas an objective of first importance. Knowledge of unusual locations for metastatic spread will reduce diagnostic delay and lead to a timely delivery of an appropriate treatment.